SVM-Based Control of Solar PV-Fed B3 Inverter for Variable Speed Induction Motor Drives - Imen Nouira El Badsi; Bassem El Badsi (IEEE Access)
Renewable energy sources (RES), particularly photovoltaic (PV) systems, have become increasingly essential for providing sustainable power solutions, especially in compact inverters designed for low-power applications such as household appliances. This paper presents two novel space-vector pulse-width modulation (SV-PWM) techniques for controlling a delta inverter coupled with an induction motor (IM) powered by PV panels. The study begins by formulating the reference voltage vector and identifying three intrinsic voltage vectors from the delta inverter. We then develop SV-PWM techniques by approximating the reference vector as a linear combination of these intrinsic vectors, followed by a detailed approach for controlling the power switches. The performance of the proposed techniques was thoroughly evaluated through comparative studies based on both simulation results and experimental measurements. The results demonstrate a significant improvement in performance, including a notable reduction in harmonic distortion, smoother electromagnetic torque ripple, and enhanced overall efficiency, compared to traditional methods, particularly during steady-state operation of the delta inverter and induction motor system.